2010
DOI: 10.1002/jhet.331
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot, three‐component synthesis of spironaphthopyrano[2,3‐d]pyrimidine‐5,3′‐indolines in water

Abstract: 0 -indoline derivatives by cyclo-condensation reaction of isatins, 2-naphthol, and barbituric acids in aqueous media is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Thus, the procedures used water as a solvent in the presence of p-TSA as a catalyst [152]. Recently, two groups of authors identified dodecyl benzenesulfonic acid (DDBSA) functionalized by silica-coated magnetic nanoparticles (γ − Fe 2 O 3 @SiO 2 -DDBSA) [153] and KAl(SO 4 ) 2 · 12H 2 O in [Bmim]PF 6 [154] as an efficient catalysts for the synthesis of a library It was shown that refluxing of a mixture of barbituric acid 264, β-naphthol 266, and isatin 114 in water in the presence of catalytic p-TSA afforded the spironaphthopyranopyrimidineindolines 267 in good yields (Scheme 75) [155]. …”
Section: Products 222mentioning
confidence: 99%
“…Thus, the procedures used water as a solvent in the presence of p-TSA as a catalyst [152]. Recently, two groups of authors identified dodecyl benzenesulfonic acid (DDBSA) functionalized by silica-coated magnetic nanoparticles (γ − Fe 2 O 3 @SiO 2 -DDBSA) [153] and KAl(SO 4 ) 2 · 12H 2 O in [Bmim]PF 6 [154] as an efficient catalysts for the synthesis of a library It was shown that refluxing of a mixture of barbituric acid 264, β-naphthol 266, and isatin 114 in water in the presence of catalytic p-TSA afforded the spironaphthopyranopyrimidineindolines 267 in good yields (Scheme 75) [155]. …”
Section: Products 222mentioning
confidence: 99%
“…With different Michael donors, diversely fused heterocycles with pyran or 1,4‐dihydropyridine moiety will be established. For example, the listed donors such as 3‐methyl‐1 H ‐pyrazol‐5(4 H )‐one , 4‐hydroxycoumarin , 4‐hydroxyquinolin‐2(1H)‐one and its N ‐allylic derivatives , cyclic 1,1‐enediamine , dimedone , 1‐(2‐phenylhydrazono)propan‐2‐one , β‐diketone or β‐ketoester , 2‐hydroxynaphthalene‐1,4‐dione , 3‐aminophenol , 2‐methyl pyrimidine‐4,6‐diol , 3‐methyl‐1 H ‐pyrazol‐5‐amine , naphthalen‐2‐amine , 1 H ‐indene‐1,3(2 H )‐dione , naphthalen‐2‐ol , and furan‐2,4(3 H ,5 H )‐dione are proved to be efficient for such protocol. Certainly, the suitable electron‐rich donors for such domino reaction are not limited to the aforementioned ones, and they can be reasonably extended to others with their functional group diversity.…”
Section: Synthesis Of Spirooxindole System Through Domino Knoevenagelmentioning
confidence: 99%
“…In continuation of our previous works on synthesis of spirooxindoles , herein, we envisioned that the use of 2‐cyanoacetamide instead of malononitrile or cyanoacetic esters in the three‐component reaction with isatins and 1,3‐dicarbonyl compounds might be a novel method to achieve new spirooxindole carboxamides 4 (Scheme ).…”
Section: Introductionmentioning
confidence: 96%